2018
DOI: 10.1111/jog.13810
|View full text |Cite
|
Sign up to set email alerts
|

Detection and genomic analysis of genital group B streptococcus in pregnant Korean women

Abstract: Direct real-time PCR using vaginal-rectal specimen could be used for detecting GBS in emergent conditions. Molecular serotypes III, Ib and V were most common. MLST analysis frequently presented ST-1, ST-19 and ST-862.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…In our study, the colonization of GBS was detected using the method of RT-PCR. Currently, there are various detection methods for GBS, including traditional culture, immunochromatographic detection, automatic microbial analysis and identification system and PCR methods [21,22]. The traditional culture method takes a long time, and its operation process is relatively difficult.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the colonization of GBS was detected using the method of RT-PCR. Currently, there are various detection methods for GBS, including traditional culture, immunochromatographic detection, automatic microbial analysis and identification system and PCR methods [21,22]. The traditional culture method takes a long time, and its operation process is relatively difficult.…”
Section: Discussionmentioning
confidence: 99%
“…This distribution is inconsistent with the recent reports on serotype distribution among young infants in Korea, in which serotypes III (44.6%), V (28.6%), and Ia (14.3%) predominated, and serotype Ib was found in only 10.7% of all cases [ 16 ]. The predominance of serotype Ib in invasive GBS infection among adults also differed from the result of a recent study on the vaginal-rectal colonization of GBS among pregnant women in Korea, in which serotype III was the most common (42.1%), followed by serotypes Ib (21.1%), V (15.8%), II (10.5%), and VI (5.3%) [ 17 ]. Based on the results of the studies involving adult patients in other countries, serotype V is among the commonly reported serotypes since the 1990s [ 5 , 18 ].…”
Section: Discussionmentioning
confidence: 69%
“…In these regions, the predominance of serotypes Ia, IV, and V has also been reported and, to a lesser extent, serotypes VI, VIII, and IX 9,27,31,32,35,50 . According to Lee et al ., 10 the prevalence and distribution of GBS depend on the region of the study. Wang et al 19 .…”
Section: Discussionmentioning
confidence: 90%